2017
DOI: 10.1097/ico.0000000000001211
|View full text |Cite
|
Sign up to set email alerts
|

Validity of Postmortem Glycated Hemoglobin to Determine Status of Diabetes Mellitus in Corneal Donors

Abstract: Postmortem HbA1c testing is feasible with current eye bank procedures and is reflective of glycemic control of donors during 90 days before death. HbA1c testing could potentially be a useful adjunct to review of the medical history and records for donor assessment for endothelial keratoplasty suitability and long-term graft success.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Having shown the effect of diabetes in the donor on both ECL and lower graft success compared with the previous literature, a randomized clinical trial seems warranted based on rigorous assessment of diabetes status of the donor. To provide greater precision in such a trial, diabetes should be better characterized in the donor as well as the recipient, by not only historical means, but also via diabetes severity grading, as well as hemoglobin A 1c testing to enable the detection of undiagnosed diabetes…”
Section: Discussionmentioning
confidence: 99%
“…Having shown the effect of diabetes in the donor on both ECL and lower graft success compared with the previous literature, a randomized clinical trial seems warranted based on rigorous assessment of diabetes status of the donor. To provide greater precision in such a trial, diabetes should be better characterized in the donor as well as the recipient, by not only historical means, but also via diabetes severity grading, as well as hemoglobin A 1c testing to enable the detection of undiagnosed diabetes…”
Section: Discussionmentioning
confidence: 99%
“…Further studies are needed to validate this finding, ideally in a randomized clinical trial. The trial should examine the impact of the severity and duration of diabetes and the systemic sequelae of diabetes on long-term graft success and endothelial cell loss 38 as well as include postmortem HbA1c testing to further characterize diabetes control and detect undiagnosed donors with diabetes 44 . Further delineating diabetes severity may not only assist in deciding which donors with diabetes are at greatest risk for graft failure; it may also address concerns on which of these donors are suitable for DMEK lenticule preparation without damaging the tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes in our corneal donors was determined from medical records and interviews of associated health care personnel and/or next of kin, if available. 1,8 Future studies are suggested to better characterize diabetes in the donor based on duration, severity 35 and HbA1c testing 36 to identify donors with diabetes whose corneas would be more prone to graft dislocation and failure following endothelial keratoplasty surgery.…”
Section: Discussionmentioning
confidence: 99%